(untitled) (Bangladesh Journal of Medical Science, 2023)
Aim: The study aims to compare the use of clinical probing and Cone Beam Computed Tomography (CBCT) in the diagnosis of furcation involvement (FI) in patients with periodontitis. Methods and materials: Twenty-two patients, aged 30 to 65 years with periodontitis were included in the study. The patients who visited from April 2021 to May 2022 were assessed based on selection criteria. A total of 135 teeth were checked for furcation involvement. Buccal, mesiopalatal, and distopalatal sites of maxillary molars and buccal and lingual sites of mandibular molars were examined clinically using a Nabers probe and radiographically by CBCT. Results: There was a significant difference between clinical and radiographic evaluations with the percentage of grade (III) cases detected with radiographic evaluation being significantly higher than that of clinical evaluation. The maxillary 1st molar 21 (60%) and maxillary 2nd molar had no furcation involvement on clinical evaluation. In Radiographic evaluation Grade I FI was more in maxillary first molars least in mandibular 2nd molar. Furcation involvement was detected clinically more on the buccal side, maxillary 1st molar and least detected at maxillary 2nd molar at MP and DP sides (0.00%) Radiographically the FI was detected more on the buccal side, maxillary 1st molar 14 (40.00%) and least detected at maxillary 1st molar at DP and MP side of maxillary 2nd molar (4.00%). Conclusion: CBCT was more reliable in the detection of grade III FI compared to clinical probing. It can be a useful tool in detecting maxillary furcations. This makes CBCT reliable in the diagnosis of furcation involvement compared to conventional methods. Dental implant planning made easy with CBCT scans as it is evaluated for its efficiency. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.87-92